A Morphological Analysis of Inflectional Morphemes in the Song Lyrics of Chase Atlantic “Chase Atlantic” Album - Inna Mustafida; Robby Satria (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study examines the use of inflectional morphemes in the Song Lyrics of Chase Atlantic “Chase Atlantic” Album. Inflectional morphemes are important linguistic elements that indicate grammatical information such as tense, number, comparison, and possession without changing the lexical category of a word. The purpose of this research is to identify the types of inflectional morphemes used in the song and to analyse the grammatical functions in communication. This research applies a qualitative descriptive approach as proposed by Creswell (2014). The data were collected through a close analysis of selected lines taken from the song lyrics. There are fourteen songs were selected and analysed to support the analysis in this article. To support the analysis, this study uses the theory of inflectional morphemes by Fromkin et al. (2013). The data are classified based on the eight types of English inflectional morphemes. The findings reveal that only seven types of inflectional morphemes appear in the song. There are present participle (-ing) appears most frequently with 81 occurrences (37.50%), followed by plural (-s) with 61 occurrences (28.24%), past tense (-ed) with 34 occurrences (15.74%), past participle (-en / -ed) with 18 occurrences (8.33%), and third person singular (-s) with 17 occurrences (7.87%). Meanwhile, comparative (-er) appears 4 times (1.85%) and superlative (-est) appear once (0.46%), while possessive (-’s) does not appear in the data (0.00%).